Pengembangan Bahan Ajar Elektronik Mata Pelajaran Praktikum Akuntansi Lembaga/ Instansi Pemerintah Kelas XI SMK Berbasis Kontekstual - Nur Aisyah Pratiwi; Agung Listiadi (Jurnal Pendidikan Akuntansi (JPAK), 2021)
The use of teaching materials has an important influence in achieving learning objectives. Teaching materials for learning must be appropriate and as needed. This research aims to produce contextual-based electronic teaching materials product, analyze the feasibility of contextual-based electronic teaching materials, and analyze students' responses to contextual-based electronic teaching materials. The 4D model by Thiagarajan, Semmel, and Semmel was used in the development process. The stages consist of define, design, and up to the development, because the disseminate stage is not carried out. The research subjects were material, linguistic, graphic expexrt, and students of class XI competency in accounting at SMKN 1 Surabaya. The types of data uses quantitative and qualitative data. Data analysis was carried out by quantitative and qualitative analysis. The results of the research from expert validation meet very feasible criteria based on the average feasibility of material, language, and graphics. The results after the product trial obtained that students responses met very understandable criteria.